Pediatric Onset Systemic Lupus Erythematosus Complicated by Toxic Epidermal Necrolysis: A Rare Association - Caguioa, Roice Angel; Go, Janelle; Tuazon, Camelia Faye; Calvarido, Mary Grace Anne (Philippine Journal of Allergy, Asthma and Immunology, 2025)
Toxic epidermal necrolysis (TEN) and systemic lupus erythematosus (SLE) rarely coexist in pediatric patients, posing significant diagnostic dilemma due to their overlapping clinical manifestations, particularly in the bullous subtype. We report a case of a 14-year-old female initially presenting with features suggestive of Bullous SLE, including generalized erythematous plaques and subsequent bullae formation, accompanied by systemic symptoms and positive serological markers for SLE. However, skin biopsy findings revealed characteristics consistent with TEN, precipitated by recent antibiotic administration for a urinary tract infection. Prompt cessation of offending medications and initiation of appropriate therapy led to clinical improvement. TEN in pediatric population with SLE is uncommon but possible occurrence. Thorough history including drug history, physical examination and proper work-up help differentiate these two or discover their coexistence.